2023
DOI: 10.2147/rmhp.s435131
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Knowledge, Attitude, and Practice Regarding Disaster Preparedness: A Cross-Sectional Study

Nermen Mohamed,
Hassanat Abdel-Aziz,
Mohamed Elsehrawy

Abstract: Background: Nations are considered to be within at hazard of crises, which create greater challenges for healthcare systems and healthcare workers. Nursing staff and student nurse play a critical role in responding to disasters, and having knowledge and a skill on disasters preparedness is crucial. The aim of the current study was to investigate the nursing students' knowledge, attitude, and practice regarding disaster preparedness. Methods: A cross-sectional study included a sample of 206 nursing students at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Meanwhile, the post program enhancements is entirely attributed to the effect of the fire preparedness and life safety program. In this stream, Saudi study (Mohamed et al, 2023), found that more than two thirds of nursing students had adequate knowledge and however, most of them had inadequate practice regarding disaster preparedness. Besides, a statistically significant relations was found between nursing students' knowledge and students' practice.…”
Section: Aim Of the Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, the post program enhancements is entirely attributed to the effect of the fire preparedness and life safety program. In this stream, Saudi study (Mohamed et al, 2023), found that more than two thirds of nursing students had adequate knowledge and however, most of them had inadequate practice regarding disaster preparedness. Besides, a statistically significant relations was found between nursing students' knowledge and students' practice.…”
Section: Aim Of the Studymentioning
confidence: 95%
“…A dissimilar result reported in Thailand by Musigapong and Phanprasit (2013), who claimed that students acquainted information from multimedia such as television, teacher, newspaper, and internet. Also, Saudi study (Mohamed et al, 2023) declared that social media apps was the most frequent source of information (78.8%), followed by the internet (69.7%), family and friends (52.3%), books and school resources (43.7%), and television (32.4%). As to preparatory school students' knowledge and attitude towards fire disaster preparedness (preprogram), majority of students had unsatisfactory knowledge, and two thirds held positive attitude.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Nursing faculty members can also play a crucial role by implementing comprehensive curricula that cover all phases of disaster and its management, preparing nursing students to be proficient in disaster preparedness. 36 Future research is also warranted to determine the effectiveness of using other educational strategies on nurses’ knowledge, skills, and attitude towards disaster preparedness. The study’s implications should be disseminated widely among nurses and nursing educators to raise awareness and improve the profession’s capacity and competency through disaster management training and educational initiatives.…”
Section: Study Limitationsmentioning
confidence: 99%